Playing with LEGO®, Learning about the Library, and "Making" Campus Connections: The Rutgers University Art Library Lego Playing Station, Part One. Issue 4 (18th May 2016) - Lotts, Megan
ABSTRACT: As libraries continue to grow and change in the 21st century, we are seeing an increased emphasis on outreach, engagement, creativity, and innovation for academic libraries. These ideas are crucial to the future of academic libraries and makerspaces are one way for academic libraries to realize these ideas. Makerspaces can be affordable, don't need to take up a lot of space, and have potential to be catalysts for creating partnerships within one's community. Engaging making events can stimulate broader conversations among library patrons and library employees as well as a way for library liaisons to connect with their faculty, students, and staff.